ANALISIS RESEPSI LIRIK LAGU “33x” DARI PERUNGGU (STUDI KASUS PADA BASIS PENGGEMAR MERUNGGU) - Muhammad Anhar Salim; Arianto Arianto; Sitti Murniati Muhtar (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2024)
This study aims to discover (1) how the Merunggu fan base perceives and interprets the messages conveyed in the song '33x' by Perunggu. (2) What are the supporting factors influencing the Merunggu fan base in their reception of the song '33x' by Perunggu? In this research, data analysis is conducted utilizing the reception analysis method. Data obtained from interviews will be categorized based on the following decoding types: a) Hegemonic-Dominant Position. b) Negotiated Position. c) Oppositional Position. The interview results will be analyzed and employed as the foundation for this study's conclusions. The results of the study describe the reception of the Merunggu fan base regarding the message content of the song '33x' by Perunggu and identify the supporting factors influencing the Merunggu fan base in their reception of the song '33x' by Perunggu. Stuart Hall's reception analysis classifies reception into three models: dominant position, negotiated position, and oppositional position. The dominant position aligns with the lyrical message, the negotiated position aligns with a personal understanding, and the oppositional position opposes the message. Several factors influence informants' reception of the song lyrics, including cultural factors, personal experiences, the musical approach, and religious factors. Through these two points, it is hoped to provide valuable data for similar research and to illustrate how Perunggu can understand how their fan base receives the messages in their song lyrics.